Hubungan Penggunaan Gadget Terhadap Perkembangan Sosial Pada Siswa Kelas 6 Di SDN Ciater 01 - Hutasoit, Mey Lys Ceryah; Ernawilis , Ernawilis; Rizal , Lutfia Hasnakhalisha (Jurnal Kesehatan STIKes IMC Bintaro, 2023)
Introduction : Based on data from Riskesdas (2018), in Indonesia the phenomenon of social development disorders in school children reaches 69.9%. Pangastuti's study of Islamic early childhood education in 2017 shows that Novitasari and Khotimah's research in 2016 gadgets are one of the factors or stimuli that can influence children's social development, namely the habit of playing gadgets. Research Objective: To determine the relationship between the use of gadgets and social development in grade 6 students at SDN Ciater 01 South Tangerang. Research Methods: This research is a quantitative study with a cross sectional approach. The population in this study is 100 respondents, while the sample is 77 respondents. The sampling technique used is to determine the relationship between the use of gadgets and social development in grade 6 students at SDN Ciater 01, South Tangerang. Research Results: The statistical test results obtained a P value of 0.038 so that the P value <0.05, which means that Ha is accepted. Consulision: There is a significant relationship between the use of gadgets and social development in grade 6 students at SDN Ciater, South Tangerang. Suggestion: If you want to do similar research or further research, it would be better if you control all theconfounding variables, so that it will increase the accuracy of the research results.